Glencoe mathematics : - Cindy J. Boyd (Glencoe/McGraw-Hill, 1999)
This book includes 13 chapters: Chapter 1: Problem solving, algebra, and geometry; Chapter 2: Applying decimals; Chapter 3: Statistics: analyzing data; Chapter 4: Using number patterns, fractions, and percents; Chapter 5: Algebra: using integers; Chapter 6: Algebra: exploring equations and functions; Chapter 7: Applying fractions; Chapter 8: Using proportional reasoning; Chapter 9: Geometry: investigating patterns; Chapter 10: Geometry: exploring area; Chpater 11: Applying percents; Chapter 12: Geometry: finding volume and surface area: Chapter 13: Exploring discrete math and probability.